" Ibn Asfour and Grammatical Reasoning in al-Zajjajis Book Sharh al-Jumal " - الزعبي دعاء (Jadara Journal of Social Sciences, 2025)
ABSTRACT This research aims to study grammatical reasoning as addressed by Ibn Asfour (d.669 AH) in the book "Sharh Jumal Al-Zajjaji" and to clarify his stance on this phenomenon in general. The research discusses his position on Al-Zajjaji’s reasoning and his approach to presenting the grammatical evidence he relied upon .His position on Al-Zajjaji’s reasoning alternated between agreement and opposition, as he supported it in some cases and opposed it in others. Additionally, he based his reasoning on grammatical evidence derived from the Holy Quran, classical Arabic poetry, and the Prophetic Hadith. He sometimes prioritized Qur’anic evidence and occasionally followed it with poetic evidence. However, his references to the Prophetic Hadith were very limited.